2011
DOI: 10.1111/j.1365-2303.2011.00896.x
|View full text |Cite
|
Sign up to set email alerts
|

Fine needle aspiration cytology in ovarian lesions: an institutional experience of 584 cases

Abstract: FNAC has a high specificity for diagnosis of ovarian/adnexal lesions but greater experience is required for the accurate subtyping of neoplasms and sensitivity is limited by inconclusive/inadequate results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 25 publications
4
25
0
Order By: Relevance
“…On the other hand, the diagnostic accuracy for FNAC in our study was within the range reported by most of the studies like that of Bandyopadhyay et al [6], Sood et al [14], Freedman et al [4], Hemalatha et al [17], and Gupta et al [16], that were (97.06%, 98%, 96.2%, 96.3%, 92% respectively). But it was slightly higher than that reported by Khan et al [19] that was (89.9%) and Stewart et al [23] that was (86.5%), and prominently higher than that reported by Mehdi et al [13] that was (80.9%).…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…On the other hand, the diagnostic accuracy for FNAC in our study was within the range reported by most of the studies like that of Bandyopadhyay et al [6], Sood et al [14], Freedman et al [4], Hemalatha et al [17], and Gupta et al [16], that were (97.06%, 98%, 96.2%, 96.3%, 92% respectively). But it was slightly higher than that reported by Khan et al [19] that was (89.9%) and Stewart et al [23] that was (86.5%), and prominently higher than that reported by Mehdi et al [13] that was (80.9%).…”
Section: Discussionsupporting
confidence: 68%
“…It may be of importance to mention that germ cell as well as sex cord stromal tumors namely granulosa cell tumor are more likely to be typed on FNAC than surface epithelial ones. A view supported by Mathur [24] and Gupta et al [16]. In our study we didn't have cases diagnosed as sex cord stromal tumor.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Recently Gupta et al, in a retrospective study of ultrasound-guided (US) FNAC of 584 ovarian lesions evaluated that FNAC sensitivity for a diagnosis of malignancy was 85.7%, specificity 98.0%, positive predictive value 97.7%, negative predictive value 87.7% and accuracy 92.0%. They concluded that FNAC has a high specificity for diagnosis of ovarian/adnexal lesions but greater experience is required for the accurate subtyping of neoplasms and sensitivity is limited by inconclusive/inadequate results [19].…”
Section: Discussionmentioning
confidence: 99%
“…Among the available imaging modalities, ultrasonography (USG) is economical, rapid and widely available, not only providing substantial information regarding the nature of the mass but also guiding the fine-needle aspiration (FNA) with adequate precision (6). Previous studies have attempted to estimate the efficacy of image-guided FNAC in the accurate preoperative diagnosis of ovarian lesions (1,(5)(6)(7)(8). The main aim of this study was to assess the sensitivity, specificity and diagnostic accuracy of USG-guided FNAC in the distinction of neoplastic and non-neoplastic ovarian masses, considering histopathology as the gold standard.…”
Section: Introductionmentioning
confidence: 99%